Distance Learning Perspectives in The Post-Covid Reality: A Survey Study at a Polish University - Joanna STANKIEWICZ-MAJKOWSKA; Kamila RADLIŃSKA (Communications of International Proceedings, 2022)
The starting point to undertake the research problem was the need to sum up the lessons learned during COVID-19 pandemic, to systematize didactic tools applied in student remote education during this breakthrough and to explore the possibilities of incorporating these tools in the post-covid reality. The literature review on distance learning at universities does not provide a wide range of case study examples. Majority of articles tend to focus on students’ opinions about distance learning whereas teachers’ perspective is not widely discussed; lecturers and academic teachers, in particular. The main objective of the article is focused on the answer to what online tools were used in that didactic process by academic teachers at the moment of COVID- 19 outbreak and whether the pandemic brought about these tools’ expansion. The survey questionnaire was used in the study which consisted of questions about change in staff digital competences and particular tools used before, during and after pandemic, as well as opinions on organisation, technical support at university. Opinions of a small group of academic teachers conducting language classes in one of the state universities in Poland were the basis for reasoning. Teachers also introduced synchronous tools to communicate with students, which was a result of system regulations at universities. Moreover, academic teachers expanded the range of the applied tools introducing new solutions or declared to use them in the post-covid reality. In the research the question of academic teachers' digital competences self-evaluation was also analysed. The academic teachers' digital competences increased.
Keywords: online tools; higher education; COVID-19; Poland